Clinical correlates of angiographically diagnosed idiopathic pulmonary hypertension. Issue 6 (June 1990) - Gray, H H; Morgan, J M; Kerr, I H; Miller, G A
Abstract : During 1970-87 43 patients with unexplained pulmonary hypertension (mean pulmonary arterial pressure greater than 25 mm Hg) were admitted to the Brompton Hospital and classified by angiographic criteria as having either symmetrical peripheral pulmonary artery pruning (thought to represent primary plexogenic pulmonary arteriopathy), n = 21, or asymmetrical pulmonary arterial occlusions (thought to represent chronic thromboembolic disease), n = 22. Patients with symmetrical pulmonary arteriopathy had significantly higher mean pulmonary arterial pressures (67 mm Hg) at the time of presentation than those with asymmetrical pulmonary arteriopathy (49 mm Hg). Clinical distinction between these two groups was impossible. Survival from the time of diagnosis was similarly poor in the two groups (26 weeks and 38 weeks) and did not correlate with any of the haemodynamic measurements. The difficulties in making distinctions between these conditions are discussed.